A rhodamine embedded bio-compatible smart molecule mimicking a combinatorial logic circuit and 'key-pad lock' memory device for defending against information risk. (5th November 2015) - Mistri, Tarun; Alam, Rabiul; Bhowmick, Rahul; Katarkar, Atul; Chaudhuri, Keya; Ali, Mahammad
Abstract : A rhodamine-based chemosensorL C with a colorimetric response towards Al 3+ and Cu 2+ and only a fluorescence response to Al 3+ enables us to fabricate a 'key-pad-logic' function. Abstract : Organic molecules with the possibility of logic operations are highly useful building blocks for the development of molecule-based "intelligent" devices for information processing applications. We have designed herein a very simple bio-friendly chemosensor (L C ) equipped with a rhodamine fluorophore moiety. This probe showed a chromo-fluorescence response profile for Al 3+ but a colorimetric response for Cu 2+ metal. The absorption responses ofL C caused by these metal ions along with the "OFF–ON–OFF" fluorescence behavior of anL C –Al 3+ complex towards EDTA were employed for the development of a three-input and one output combinatorial molecular system. Interactions of the mentioned metal ions withL C in controlled sequential experiments gave fluorescence responses, enabling us to fabricate a 'key-pad-logic' function. So, a single molecular system performing such multiple 'Boolean' operations not only simplifies the complexity of a chemical driven 'Intelligence' device but also enriches the security of such a device against information invasion due to the sequence controlled sensor–analyte interactions and may find potential applications in biocompatible molecular logic platforms.